PENERAPAN MODEL PEMBELAJARAN TUTOR TEMAN SEBAYA UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 59 SEBANGAR KECAMATAN MANDAU - Ludhiarty Hardiana; Syahrilfuddin Syahrilfuddin; Hamizi Hamizi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem in this research is the result of social studies students in the fourth grade (IVA) SDN 59 Sebangar still low with an average value of 61.62 (with KKM 70). The purpose of this research is to improve student learning outcomes fourth grade (IVA) SDN 59 Sebangar with the implementation of Problem Based Learning model. This research is a class act with two cycles in the second half of 2014/2015. Before applying the model of Problem Based Learning average value of 61.62, after applying the Problem Based Learning model, UH I is 70.81 which increased 14.91% from the base score with an average of 61.62. UH II is 80.40 which increased 30.48%. Activity teachers with the implementation of Problem Based Learning model first dipertemuan first cycle was 55% (enough categories), and the second meeting 65% (both categories) in the second meeting, which increased by 10 points. In the second cycle, the activities of teachers in the first meeting is 80% (both categories) increased 15 points of the second meeting of the first cycle. Teacher activity to 90% (verygood category) at the second meeting, which increases 10 points. Activity of students in the first meeting of the first cycle was 55% (enough categories), and 70% (both categories) in the second meeting, which improved 15 points. In the second cycle, the activity of students in the first meeting is 80% (both categories) increased 10 points of the second meeting of the first cycle. The second meeting of the second cycle was 95% (verygood category) which increases 15 points. Application of Problem Based Learning model can improve student learning outcomes fourth grade (IVA) SDN 59 Sebangar.Key Words: Problem Based Learning Model, IPS Learning Outcomes